Meningkatkan Kapasitas Sistem Administrasi Pemerintah Untuk Kepentingan Bangsa dan Persaingan Global - Maria Rosarie Harni Triastuti (Jurnal Administrasi Publik, 2008)
Global competitive and change era not only demand government bureaucracy being more self-introspection, but also capable to enhance government administration system capacity which has quality and ability to compete. Government administration system enhancing strategy must be done in individual, group, organization and management contexts as a sustainability system to increase competency and ability to solve problem. Implementation of this strategy will be succes if supported by outer shifts and inner shifts in the contexts of four components said early before.Keywords: change, administration system capacity, enhancing strategy